Effects of medication reviews on use of potentially inappropriate medications in elderly patients; a cross-sectional study in Swedish primary care - Cecilia Lenander; Åsa Bondesson; Nina Viberg; Anders Beckman; Patrik Midlöv (BMC, 2018)
Abstract Background Drug use among the elderly population is generally extensive and the use of potentially inappropriate medications (PIMs) is common, which increases the risk for drug-related problems (DRP). Medication reviews are one method to improve drug therapy by identifying, preventing and solving DRPs. The aim of this study was to evaluate the effect of medication reviews on total drug use and potentially inappropriate drug use in elderly patients, as well as describe the occurrence and types of drug-related problems. Method This was a cross-sectional analysis to study medication reviews conducted by trained clinical pharmacists followed by team-based discussions with general practitioners (GPs) and nurses, for elderly primary care patients in Skåne, Sweden. Included in the analysis were patients ≥75 years living in nursing homes or in their own homes with home care, who received a medication review during 2011-2012. Documented DRPs were described as both the type of DRPs and as pharmacists' recommendations to the GP. The usage of ≥3 psychotropics and PIMs (antipsychotics, anticholinergics, long-acting benzodiazepines, tramadol and propiomazine) at baseline and after medication review were also studied. Results The analysis included a total of 1720 patients. They were on average aged 87.5 years, used typically 11.3 drugs (range 1-35) and 61% of them used 10 drugs or more. Of the patients, 84% had at least one DRP with a mean of 2.2 DRPs/patient. Of the DRPs, 12% were attributable to PIMs. The proportion of patients with ≥ one PIM was reduced significantly (p < 0.001) as was the use of ≥3 psychotropics (p < 0.001). The most common DRP was unnecessary drug therapy (39%), followed by dose too high (21%) and wrong drug (20%). Drug withdrawal was the most common result. Conclusion This study shows that medication reviews performed in everyday care are one way of improving drug use among elderly patients. The use of potentially inappropriate medications and use of three or more psychotropic drugs decreased after the medication review. Our study also shows that drug use is extensive in nursing home residents and elderly patients with homecare, and that unnecessary drug therapy is a common problem.